The Influence of Empowerment and Self-Efficacy on Employee Performance - Mansyur, Nadhila Adelfrini (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
The aims of the research to find the influence of empowerment and self-efficacy on employee performance. This study employs a qualitative and quantitative approach. Empowerment has a significant impact on the performance of employees. The presence of self-efficacy has been found to have a favorable impact on the performance of employees. It is evident that employees consistently exhibit a sense of competence, perceiving themselves as capable of successfully accomplishing any task. Moreover, they hold the belief that their skills are on par with, if not surpassing, those of their colleagues.